Sonochemical Production of Nanomaterials - Okitsu, Kenji (Ultrasound and Sonochemistry,, 2018)
This book discusses the ultrasonic synthesis, characterization and application of various nanoparticles, as well as the ultrasonic synthesis of metal and inorganic nanoparticles such as noble metals, transition metals, semiconductors, nanocomposites, alloys and catalysts. In addition, it describes the engineering of micro- and nanosystems using ultrasound-responsive biomolecules. In acoustic cavitation, unique phenomena based on bubbles dynamics, extreme high-temperature and pressure conditions, radical reactions, extreme heating and cooling rates, strong shockwaves, and microstreaming are generated, and under certain conditions, mist generation (atomization of a liquid) is effectively induced by ultrasonic irradiation. These unique phenomena can be used to produce various high-performance functional metal and inorganic nanoparticles. Nanoparticles and nanomaterials are key materials in advancing nanotechnology and as such ultrasound and sonochemical techniques for producing nanoparticles and nanomaterials have been actively studied for the last two decades. Although a few professional books related to "ultrasound" and "nanomaterials" have been published, these mainly target professional researchers. This book covers this topic in a way that appeals to graduate students, researchers and engineers.